Konsentrasi Karbon Dioksida di Dalam Ruangan dan Kejadian Sick Building Syndrome pada Pekerja Kantor: Tinjauan Pustaka - Mira Anggraini; Yuanita Windusari; Hamzah Hasyim (Buletin Keslingmas, 2026)
Indoor Air Quality (IAQ) is the concentration of carbon dioxide (CO₂), which reflects the effectiveness of ventilation systems. Elevated levels of CO₂ are often associated with the occurrence of Sick Building Syndrome (SBS), a collection of symptoms such as headaches, fatigue, eye irritation, and concentration problems experienced by building occupants. This study is a structured literature review conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for reporting the process of article identification and selection.The keywords used were “carbon dioxide,” “indoor air quality,” “sick building syndrome,” and “office workers.” From the eight studies reviewed, five (62,5%) reported a significant association between elevated CO₂ concentrations and the incidence of Sick Building Syndrome, while three (37,5%) found no statistically significant relationship. Most studies indicated that CO₂ concentrations exceeding 1000 ppm were correlated with an increase in SBS symptoms, particularly headaches, fatigue, and respiratory irritation. Other factors such as temperature, humidity, and ventilation effectiveness were also found to influence the relationship. Most studies indicate an association between increased CO₂ concentrations and the occurrence of Sick Building Syndrome (SBS) symptoms, although results across studies still show some variation. Monitoring CO₂ levels can serve as an indicator of indoor air quality and as an early preventive measure against SBS. Improved ventilation management and air quality control policies are essential to create healthier and more productive indoor working environments.